$λ$-Euler's Difference Table for Colored Permutations - Han, Bin (The Electronic Journal of Combinatorics, 2018)
Motivated by the $λ$-Euler's difference table of Eriksen et al. and colored Euler's difference table of Faliharimalala and Zeng, we study the $λ$-analogue of colored Euler's difference table and generalize their results. We generalize the number of permutations with $k$-excedances studied by Liese and Remmel in colored permutations. We also extend Wang et al.'s recent results about $r$-derangements by relating with the sequences arising from the difference table.